علوم القرآن عند الإمام ابن بركة من خلال كتاب الجامع: دراسة منهجية مقارنة - الصوافي, سعيد بن راشد (مكتبة خزائن الآثار, 2020)
Keywords: Enseignement -- Oman

Science Education in Oman: Taking Oman to Better Future - Ambusaidi, Abdullah K.; Shahat, Mohamed A.; Al Musawi, Ali S. (Science Education in Countries Along the Belt & Road: Future Insights and New Requirements, 2022)
The purpose of the present chapter is to give the reader an overview of the current science education research in Oman. The chapter focuses on three main sections as an overview of the country, an overview of the education development, and the current situation of science education. It addresses the emerging technologies in relation to science education including blended education and e-learning developments. The chapter then discusses the requirements for better implementation of science education along with the future strategies to overcome the challenges and issues that facing science teachers in Oman. It concludes by recommending the importance of making greater efforts to instill the twenty-first-century skills in the future graduates of science to enable them to respond to the requirements of the global economic market.
Keywords: Enseignement -- Oman

On the fiqh of Education – Traditional School Organisation and Religious Pedagogy in Oman. The Example of Shaykh Jāʿid b. Khamīs al-Kharūṣī (d. 1237/1822) and fiqh al-madrasa - Bouzenita, Anke Iman; Jabri, Khalfan al- (Hikma: Journal of Islamic Theology and Religious Education, 2021)
Keywords: Enseignement -- Oman

الرسوم التعليمية في الذاكرة العمانية - الشيباني, سلطان بن مبارك (الذاكرة, 2023)
Keywords: Enseignement -- Oman

المدارس التعليمية العمانية ‏من القرن الأول الهجري إلى العصر الحديث (‏دراسة توفيقية وصفية) ‏مدارس نموذجية - الصوافي, سعيد بن راشد; الوهيبي, مسلم بن سالم; السالمي, محسن بن ناصر; البوسعيدي, خلفان بن سالم (مكتبة الجيل الواعد, 2021)
Keywords: Enseignement -- Oman